G29 A Case of Phylloid Hypomelanosis – a Rare But Specific Presentation of Chromosomal Mosaicism. (4th June 2013) - Solman, L; Glover, M; Kinsler, VA
Abstract : This 18 month old boy presented with a history of hypopigmented macular lesions, mild neurodevelopmental delay and recurrent episodes of acrocyanosis with tachycardia and increased tone. The cutaneous lesions developed from the age of 3 months, affecting the right trunk and right upper and lower limbs. Examination revealed large well-defined hypopigmented macules in a classical phylloid pattern, with a midline cut-off anteriorly and posteriorly on the trunk, compatible with a diagnosis of phylloid hypomelanosis. Mild facial dysmorphism was noted. Neurodevelopmental assessment at the age of 12 months suggested mild global delay; EEG and MRI of the CNS are pending. Cardiovascular examination was normal, however 24 hour ECG revealed non-specific ST segment changes. Ophthalmologic assessment was normal. Array comparative genomic hybridisation on a peripheral blood sample was normal. Karyotyping of affected and unaffected skin fibroblasts is underway. Phylloid hypomelanosis (Greek phyllon = leaf, eidos = form) is characterised by congenital hypopigmented macules resembling a floral ornament, with round, oval or oblong patches (1), distinct from the commoner Blashko-linear distribution. It is a rare but highly specific sign of chromosomal mosaicism, universally associated thus far in the literature with mosaicism for duplications of 13q (1.2). Associated extracutaneous anomalies vary, and can include neurological, ocular, dental and skeletal defects (2). Cardiovascular abnormalities have not been reported thus far, and follow-up in our patient will clarify whether this is an associated or incidental feature. Affected individuals require multi-disciplinary assessment and long-term follow-up. As this is a somatic mosaic condition the possibility of fully affected offspring from the probands should be addressed at an appropriate age. References: Phylloid hypomelanosis is closely related to mosaic trisomy 13. Happle R. Eur J Dermatol. 2000 Oct-Nov; 10(7):511–2. Phylloid hypomelanosis and mosaic partial trisomy 13: two cases that provide further evidence of a distinct clinicogenetic entity. González-Enseñat MA, Vicente A, Poo P, Catalá V, Mar Pérez-Iribarne M, Fuster C, Geán E, Happle R. Arch Dermatol. 2009 May; 145(5):576–8.